The School Children of Mining Workers of Almaden. An example of manjonian teaching - Almansa Rodriguez, Emiliano; Hernández Sobrino, Angel Manuel (Historia y Memoria de la Educación, 2020)
Ave Maria Schools were founded in Granada in 1889 by the priest and educator Andrés Manjón. Unlike the traditional method of infant education in those years, Father Manjón centered pedagogy in the Catholic religion, considering nature as God’s work. In his concept, play, manual labor and outdoor teaching were good Christians in a happy environment so that they would later join the working world. They quickly spread throughout Spain and other countries, Ave Maria Schools are considered a pioneering experience of teaching in their time and enjoyed great social prestige. In the subsoil of Almadén, the largest mercury deposit in the world was exploited from the Arab domination, with 2,500 workers working in the first half of the 20th century. The School of Children of Workers had been founded in 1908, but in 1926, coinciding with the proclamation of the dictatorship of Primo de Rivera, it was transformed into a Manjonian school. Become a secular school during the Second Republic and the subsequent civil war, he returned to act as a school of Ave Maria from 1939 until the 1960s. Minas de Almadén, like other large mining and industrial companies in northern Spain, exercised a paternalistic strategy with its operators and chose religious education as the most appropriate for the formation of their children.